Phytochemical screening and bioactivity studies of ziziphus mauritiana (twigs and leaves) / Saidatul Aqilah Mohamad Yusof - Mohamad Yusof, Saidatul Aqilah (2017)
In the research of phytochemical screening and bioactivity studies of Ziziphus mauritiana, two part of Z. mauritiana plant were obtained which are leaves and twigs. Extraction process of Z. mauritiana take placed by using three different polarity of solvents which are hexane, chloroform and methanol using cool extraction method. The highest percentage yield is chloroform leave extract which is 3.71%. The phytochemical screening studies revealed there are many secondary metabolites presence inside Z. mauritiana such as alkaloid, flavonoid, glycoside, phenol, saponin, steroid, sterol, tannin and terpenoid while for leave part saponin was absence. In thin layer chromatography (TLC) method the solvent system used is the mixture of hexane and chloroform with ratio 3:7 and 1:9 to obtain better fractionation of compound using short (245 nm) and long (366 nm) wavelength Ultraviolet (UV) lamp. Antibacterial activity by using disc diffusion method toward Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Salmonella sp. were conducted. Besides that, the highest maximum zone inhibition diameter recorded is hexane leaves crude extract on S. aureus bacteria which is 15 mm. In addition, antioxidant study discovered the highest percentage found on crude extract of methanol.